Burkina Faso’s agrifood system structure and drivers of transformation - Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Diao, Xinshen; Ellis, Mia (International Food Policy Research Institute, 2023)
Burkina Faso experienced strong annual economic growth of 6.0 percent between 2009 and 2019 (NISD 2021). However, the global COVID-19 pandemic caused a significant slowdown in economic growth in 2020, while an increase in armed insurgencies by domestic terrorist groups also had an adverse effect on the economy. Burkina Faso’s GDP growth is projected to reach 5.0 percent in 2023 and 5.3 percent in 2024 (World Bank 2023), suggesting the economy is unlikely to return to its pre-pandemic growth trajectory. Agriculture remains an important sector, accounting for one-fifth of GDP and nearly half of employment in Burkina Faso. The agriculture sector also performed well, growing at around 5 percent annually in the 2009 to 2019 period (NISD 2021). In this brief, we look beyond primary agriculture to understand how Burkina Faso’s broader agrifood system (AFS) is contributing to growth and transformation in the country.